CEO features, foreign ownership, and real earnings manipulation: evidence from Jordan - Safia Abdo Ali Al-Begali; Lian Kee Phua; Magdi Abdoh Al-Rowaidi (Cogent Economics & Finance, 2024)
This study investigates the impact of foreign ownership (FOR) on the relationship between CEO features and real earnings management (REM) practices, including abnormal cash flow from operating (ACO), abnormal discretionary expenses (ADIET), abnormal production costs (APRC), and aggregate REM. Using the Feasible Generalized Least Squares (FGLS) method, regressions were performed using 685 enterprise-year observations of enterprises listed on the Amman Stock Exchange from 2017 to 2021. The findings reveal that female CEOs restrict REM (APRC), while CEOs with prior experience engage more in REM by manipulating sales, reducing discretionary expenses, and engaging in aggregate REM to establish a positive reputation. Additionally, it was found that CEOs with longer tenures are less likely to engage in REM (ADIET and APRC). Furthermore, enterprises with older CEOs have a mitigating effect on aggregate REM practices, although they are more inclined to engage in REM by reducing discretionary expenses. Consistent with the knowledge spillover hypothesis, foreign ownership acts as a constraint on the practice of REM. Specifically, when combined with CEO tenure, foreign ownership limits REM (ACO and aggregate REM). However, in line with the information asymmetry hypothesis, the study reveals that foreign ownership, in combination with CEO gender, increases REM (ACO). Moreover, foreign ownership increases REM (ADIET) when combined with CEO experience. Additionally, the results indicate that foreign ownership intensifies REM (ACO and aggregate REM) when combined with CEO age. This study provides new insights into the impact of foreign ownership (FOR) on the relationship between CEO features and REM practices, demonstrating that foreign ownership can either limit or intensify REM practices depending on the specific combination of CEO features, such as gender, experience, tenure, and age. These findings will benefit practitioners, investors, and regulators by enhancing their understanding that enterprises with significant FOR and longer CEO tenure tend to demonstrate higher financial reporting quality (FRQ) and employ lower levels of REM. This study highlights how foreign ownership (FOR) affects the relationship between CEO features (CEO gender, experience, tenure, and age) and REM, namely, abnormal cash flow from operating (ACO), abnormal discretionary expenses (ADIET), abnormal production costs (APRC), and aggregate REM. It provides evidence that CEOs who are female tend to decrease REM through sales manipulation, and CEOs experience increased REM through manipulating sales, reducing discretionary expenses, and engaging in aggregate REM. Additionally, it was found that CEOs with longer tenures are less likely to engage in REM through discretionary expenses and overproduction. Also, enterprises with older CEOs have a mitigating effect on aggregate REM practices, although they are more inclined to engage in REM by reducing discretionary expenses. The results revealed that foreign ownership could limit or intensify REM practices depending on the combination of CEO features, such as gender, experience, tenure, and age. These findings will benefit practitioners, investors, and regulators by enhancing their understanding that the interaction between foreign ownership and CEO tenure further contributes to restricting REM (ACO and aggregate REM).
Keywords: 330; CEO features; REM; foreignownership; Jordanian enterprises